Vertigo 42 [large type] : a Richard Jury mystery - Grimes, Martha (Grimes, Martha. Richard Jury mystery., 2014)
"At Vertigo 42, a bar high above London's financial district, Richard Jury meets Tom Williamson - a friend of a friend who is convinced his wife, Tess, was murdered 17 years ago. Tess's death was ruled accidental - a fall caused by vertigo - but Jury agrees to re-examine the case. A young girl's fatal fall at a children's party 22 years ago at Tom and Tess's home may be connected. After an elegantly dressed woman falls from a tower near a pub that Jury and his cronies frequent, and her estranged husband is later found dead, Jury begins to suspect that the now grown "children" from Tess's ill-fated party are the key to solving these interwoven mysteries"--